A Taguchi optimization of stir casting process parameters for graphene nanoplatelets/ A356 alloy composite - Afifah Md Ali; Mohd Zaidi Omar; Mohd Shukor Salleh; Intan Fadhlina Mohamed (Fakulti Kejuruteraan ,UKM,Bangi., 2024)
Aluminum metal matrix composite (AMC) is a potential material for diverse applications in the field of automotive and aerospace owing to their superior mechanical properties, lightweight behavior, and low thermal expansion. Graphene nanoplatelets (GNP) have emerged as the preferred reinforcement in AMC. They are incorporated into the matrix by stir-casting methods to generate semi-solid feedstock suitable for thixoforming. The effects of the stirrer parameter and GNP content were examined using Taguchi design of experiments with an L8 (23) orthogonal array. The parameters tested were stirring speed (300-500rpm), GNP content (0.3- 0.7 wt%) and stirring time (5-10 minutes). The signal-to-noise ratio (S/N) and hardness of the GNP /A356 composite were used as response variables. The contribution of three factors in enhancing hardness has been identified. The optimum parameter obtained with stirring speed, GNP content, and stirring time is 500rpm, 0.7wt.%GNP and 5 min respectively.